Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1103/physreva.96.043608
|View full text |Cite
|
Sign up to set email alerts
|

Low-lying excitation modes of trapped dipolar Fermi gases: From the collisionless to the hydrodynamic regime

Abstract: By means of the Boltzmann-Vlasov kinetic equation we investigate dynamical properties of a trapped, one-component Fermi gas at zero temperature, featuring the anisotropic and long-range dipole-dipole interaction. To this end, we determine an approximate solution by rescaling both space and momentum variables of the equilibrium distribution, thereby obtaining coupled ordinary differential equations for the corresponding scaling parameters. Based on previous results on how the Fermi sphere is deformed in the hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 87 publications
(220 reference statements)
0
18
0
Order By: Relevance
“…Indeed, the quantum-mechanical expectation values of the system observables, which are required for the calculation of the properties of nonrelativistic quantum systems based on exact diagonalization, can be obtained as their phase-space averages, weighted by the Wigner function. In the case where the dipolar orientation axis lies along one of the trapping axes, an accurate ansatz for the Wigner function takes the simple form [38][39][40][41][42][43][44][45][46][47] r R…”
Section: Wigner Function In Equilibriummentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, the quantum-mechanical expectation values of the system observables, which are required for the calculation of the properties of nonrelativistic quantum systems based on exact diagonalization, can be obtained as their phase-space averages, weighted by the Wigner function. In the case where the dipolar orientation axis lies along one of the trapping axes, an accurate ansatz for the Wigner function takes the simple form [38][39][40][41][42][43][44][45][46][47] r R…”
Section: Wigner Function In Equilibriummentioning
confidence: 99%
“…This ansatz is motivated by the Fermi-Dirac distribution of a noninteracting Fermi gas at zero temperature, whose Wigner function has the above form. A theory based on the above ansatz [38,47] was successfully used to determine the deformation of the FS, while its extension [46] enabled a detailed analysis of the ground state and the time-offlight (TOF) expansion dynamics of the system for different collisional regimes. Furthermore, numerical comparisons [59,60] have confirmed that, even in the case of polar molecules with masses of the order of 100 atomic units and an electric dipole moment as large as 1D, the above variational ansatz yields highly accurate results, within a fraction of per mille.…”
Section: Wigner Function In Equilibriummentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, for a rapidly rotating 2D system of dipolar fermions the Wigner crystal phase is possibly the ground state for low densities, while for higher densities it turns into a Laughlin liquid state [43,44]. Further studies focused on finite-temperature effects [27,[45][46][47][48], dynamical properties in the collisionless and hydrodynamic regimes [49][50][51][52][53][54][55], bilayer configurations [56][57][58][59], and quench dynamics [60]. However, less attention has been paid to the quasiparticle properties in the Fermi liquid phase beyond the mean-field level.…”
Section: Introductionmentioning
confidence: 98%